Biomechanical comparison of successful snatch and unsuccessful frontward barbell drop in world-class male weightlifters - Nagao, H.; Huang, Z.; Kubo, Y. (Sports Biomechanics, 2023)
This study aimed to clarify the success factor of snatch based on barbell trajectory and lifter's motion among elite male weightlifters. Motion analysis of snatch was conducted using digital videos recorded at the 2015 World Weightlifting Championships. Data on successful and unsuccessful snatch lifts of 22 lifters, each using the same weights, were analysed; the unsuccessful lift was due to a frontward barbell drop. Results revealed that the difference in backward barbell displacement between the turnover to catch phase (DxL) and peak backward barbell velocity (pVx-) was significantly greater in successful snatch than in frontward barbell drops (DxL: p <0.001, d >5.0, pVx-: p <0.01, d >2.0). Backward displacement of the lifters' centre of mass (COM) between the transition to turnover phase in a successful snatch lift was significantly smaller than that in an unsuccessful lift (p<0.05, d >2.0). It is considered that there was excessive backward leaning during unsuccessful lifts. However, no significant difference in maximum barbell height (Dy1) was found. Based on these findings, DxL and pVx- are success factors for snatch, whereas Dy1 is not. It is suggested that avoiding excessive backward-leaning of the body in the turnover phase may vary the chances of successful snatch among elite male weightlifters.